A handheld flow genetic analysis system (FGAS): towards rapid, sensitive, quantitative and multiplex molecular diagnosis at the point-of-care level1. Issue 12 (21st June 2015) - Shu, Bowen; Zhang, Chunsun; Xing, Da
<x xml:space="preserve">Abstract</x> An ultra-compact, battery-powered and easy-to-use microfluidic platform is proposed for rapid, sensitive, multiplex and real-time quantification and point-of-care genetic analysis.